New concepts in breeding barn design - Levis, D.G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Many existing swine breeding facilities have been designed to control the environment, provide continuous boar-sow contact for stimulating recently weaned sows to cycle, reduce the distance a weaned sow or boar has to be moved for mating, and reduce construction costs by not constructing breeding pens to be used only for mating. Pork producers operating these types of facilities have had problems with efficiency and accuracy of estrous detection, low percentage (70%) of sows bred twice, slick breeding floors, and excessive labor requirements. A breeding facility should be arranged so the work routines, such as estrous detection; moving, mating, and feeding animals; and recording breeding information arc easily, quickly, and safely performed. Remember, tasks that are difficult to do may never be done.
Keywords: Swine; Facilities; Breeding; Sow